After Sex? : On Writing since Queer Theory - Parker, Andrew, 1953-; Halley, Janet E., 1952- (Book collections on Project MUSE., 2011)
Prominent participants in the development of queer theory explore the field in relation to their own intellectual itineraries, reflecting on its accomplishments, limitations, and critical potential.